Assessment of Hepatitis B Awareness Among High School Students - Balin, Safak Ozer; Denk, Affan (Aves, 2016)
Objective: The objective of this study was to assess hepatitis B awareness levels among high school students, who compose a risk group for HBV. Methods: A cross-sectional study was carried out by the participation of 371 students from central high school in Aricak town, in Elazig province in May 2015. After getting permission from school administration, the questionnaire was applied to the students who were informed beforehand. In the questionnaire for measuring the awareness of students about hepatitis B, there were 25 questions and assessment was performed out of 100 points by giving 4 points to each question. For statistical analysis, IBM SPSS Statistics for Windows. Version 22.0 (Statistical Package for the Social Sciences, IBM Corp., Armonk, NY, USA) program was used. Results: Among 371 participants, 152 (41%) were female and 219 (59%) were male. The average age of the students was found to be 16.14 +/- 1.35 (minimum=14, maximum=22). The awareness point average of the students about hepatitis B was 34.05 (min=0, max=76). It was determined that awareness points of male and female students were similar (p=0.56). It was observed that awareness point average of ninth grade students was higher than the students in senior grades (p=0.009). The most frequently acquired correct answer related to hepatitis B was It is a blood-borne disease given by 200 (53.9%) students. Conclusions: The awareness levels of high school students about hepatitis B including general information, mode of transmission and prophylaxis are not sufficient. Therefore, it is important to plan training programs and to form health policies so as to increase the awareness level.
Lise öğrencilerinin hepatit B konusundaki bilgi düzeylerinin değerlendirilmesi
Keywords: Hepatitis B; awareness